Chapter Four: Protecting an Ecosystem Service: Approaches to Understanding and Mitigating Threats to Wild Insect Pollinators - Gill, Richard J; Baldock, Katherine C.R; Brown, Mark J.F; Cresswell, James E; Dicks, Lynn V; Fountain, Michelle T; Garratt, Michael P.D; Gough, Leonie A; Heard, Matt S; Holland, John M; Ollerton, Jeff; Stone, Graham N; et al. (Advances in ecological research, 2016)
Insect pollination constitutes an ecosystem service of global importance, providing significant economic and aesthetic benefits as well as cultural value to human society, alongside vital ecological processes in terrestrial ecosystems. It is therefore important to understand how insect pollinator populations and communities respond to rapidly changing environments if we are to maintain healthy and effective pollinator services. This chapter considers the importance of conserving pollinator diversity to maintain a suite of functional traits and provide a diverse set of pollinator services. We explore how we can better understand and mitigate the factors that threaten insect pollinator richness, placing our discussion within the context of populations in predominantly agricultural landscapes in addition to urban environments. We highlight a selection of important evidence gaps, with a number of complementary research steps that can be taken to better understand: (i) the stability of pollinator communities in different landscapes in order to provide diverse pollinator services; (ii) how we can study the drivers of population change to mitigate the effects and support stable sources of pollinator services and (iii) how we can manage habitats in complex landscapes to support insect pollinators and provide sustainable pollinator services for the future. We advocate a collaborative effort to gain higher quality abundance data to understand the stability of pollinator populations and predict future trends. In addition, for effective mitigation strategies to be adopted, researchers need to conduct rigorous field testing of outcomes under different landscape settings, acknowledge the needs of end-users when developing research proposals and consider effective methods of knowledge transfer to ensure effective uptake of actions.